PERAN KOMITMEN AFEKTIF DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA SDM - Atmaja, Hanung Eka; Ratnawati, Shinta (JAB (Jurnal Akuntansi & Bisnis), 2019)
In achieving organizational goals, human resources have a very important role in addition to other resources that the organization has. Study of organizational behavior suggests there are three determinants of behavior in organizations, namely individuals, groups, and structures. The third effect was studied on the organization with the aim to apply knowledge to improve effectiveness in an organization.To assess the quality of existing human resources can be measured by employee performance. Organizations must believe that to achieve excellence it is necessary to seek the highest individual performance, one of which is through affective commitment and organizational citizenship behavior.Â Keywords: HRM Performance, Affective Commitment, Organizational Citizenship Behavior